Application of AP-MALDI Imaging Mass Microscope for the Rapid Mapping of Imipramine, Chloroquine, and Their Metabolites in the Kidney and Brain of Wild-Type Mice - Ariful Islam; Takumi Sakamoto; Qing Zhai; Md. Muedur Rahman; Md. Al Mamun; Yutaka Takahashi; Tomoaki Kahyo; Mitsutoshi Setou (MDPI AG, 2022)
Mass spectrometry imaging (MSI) is well-known for the non-labeling visualization of analytes, including drugs and their metabolites in biological samples. In this study, we applied three different tools of MSI, desorption electrospray ionization (DESI)-MSI, matrix-assisted laser desorption ionization (MALDI)-MSI, and a newly developed atmospheric pressure (AP)-MALDI-MSI known as iMScopeTM QT for rapid mapping of imipramine, chloroquine, and their metabolites in C57BL/6 male wild-type mice. Among three MSI tools, better detection capability for targeted drugs at higher speed (up to 32 pixels/s) was observed in iMScope QT. It revealed that imipramine and its metabolites were significantly accumulated in the renal cortex of mice, but chloroquine and its metabolites were highly accumulated in the renal pelvis and renal medulla of mice. Additionally, a higher accumulation of imipramine was noted in the thalamus, hypothalamus, septum, and hindbrain of mice brains. However, chloroquine and its metabolites showed notable accumulation in the lateral ventricle, fourth ventricle, and fornix of the mice brains. These findings of our study can be helpful in understanding clinically relevant properties, efficacy, and potential side effects of these drugs. Our study also showed the potentiality of iMScope QT for rapid mapping of small drugs and their metabolites in biological samples.